Variation in reproductive systems facilitates species boundaries of sympatric Vriesea (Bromeliaceae) - Neri, Jordana; Wendt, Tânia; Leles, Bruno [UNESP]; Dos Santos, Manoel Francisco; Palma-Silva, Clarisse [UNESP] (Oxford University Press (OUP), 2017)
Divergence in reproductive systems among plant species often involves changes in floral traits. The distance separating stigmas and anthers (herkogamy) directly affects the relative importance of reproduction by outcrossing vs. selfing reproduction and can impact the integrity of sympatric species. We studied the reproductive biology of two closely related Vriesea spp. and investigated the variation in herkogamy among sympatric and allopatric populations and their implication in mating system variation and reproductive isolation between sympatric sister species. Both species are self-compatible, but differ in reproductive systems. Reduction in herkogamy drives a higher incidence of selfing for V. scalaris, whereas V. simplex relies predominantly on outcrossing events. Manual interspecific crosses produced F1 hybrids and confirmed natural hybridization previously observed between these two species. The closer anther-stigma positioning may be related to a higher capacity for autonomous selfing and might be one possible reproductive barrier facilitating sympatric species coexistence.
Keywords: Herkogamy; Hybridization; Outcrossing; Pre- and postzygotic barriers; Reproductive isolation; Selfing